2020
DOI: 10.1302/2633-1462.16.bjo-2020-0053.r1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and orthopaedic team members’ mental health during the COVID-19 pandemic

Abstract: Aims Healthcare systems have been rapidly restructured to meet COVID-19 demand. Clinicians are working to novel clinical guidelines, treating new patient cohorts and working in unfamiliar environments. Trauma and orthopaedics (T&O) has experienced cancellation of routine clinics and operating, with redistribution of the workload and human resources. To date, no studies have evaluated the mental health impact of these changes on the T&O workforce. We report the results of a novel survey on the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
0
14
1
4
Order By: Relevance
“…The impact of fellowship training or a senior post is another significant stressor that remains inconclusive. Thakrar et al 11 demonstrated a lesser level of psychological impact in associate consultants as compared to station health officer or other junior staff. The extrapolation of this scenario in the context of subspecialisation leading to minimal levels of anxiety remains to be proven, as in our study we did not observe any such significant association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of fellowship training or a senior post is another significant stressor that remains inconclusive. Thakrar et al 11 demonstrated a lesser level of psychological impact in associate consultants as compared to station health officer or other junior staff. The extrapolation of this scenario in the context of subspecialisation leading to minimal levels of anxiety remains to be proven, as in our study we did not observe any such significant association.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants was based on the sample size calculation for cross-sectional studies 13 and past studies from the literature. [11][12][13][14] This method drew on Facebook's inherent peer network structures to encourage users to recruit other orthopaedic surgeons who may or may not be on Facebook. 15 Participants were invited through three online venues: public ('wall') posts advertising our research survey on some orthopaedic groups; peer referral on Facebook and What-sApp group messages from 2 May to 16 May 2020.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased working hours and/or a stressful working environment have been reported to be important risk factors affecting human orthopedic surgeons' mental health. [30][31][32] Depression, anxiety and burn out have been reported to affect up to 22.8%, 23.2% and an average of 40% of orthopedic surgeons respectively. 33 This is directly transferable to veterinarians; veterinary surgeons' mental health should not be overlooked, as our professions' suicide rate is a least 3 times that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of unnecessary or unjustified interventions on personnel strain and workload should also not be taken lightly. Increased working hours and/or a stressful working environment have been reported to be important risk factors affecting human orthopedic surgeons' mental health 30–32 . Depression, anxiety and burn out have been reported to affect up to 22.8%, 23.2% and an average of 40% of orthopedic surgeons respectively 33 .…”
Section: Discussionmentioning
confidence: 99%